To rewrite the quadratic function \( y = 3x^2 - 48x + 195 \) in vertex form by completing the square, follow these steps:
-
Factor out the coefficient of \( x^2 \) from the \( x^2 \) and \( x \) terms: \[ y = 3(x^2 - 16x) + 195 \]
-
Complete the square for the expression \( x^2 - 16x \):
- Take half of the coefficient of \( x \) (which is \(-16\)), square it, and add and subtract it inside the parentheses. Half of \(-16\) is \(-8\), and \((-8)^2 = 64\). \[ y = 3(x^2 - 16x + 64 - 64) + 195 \] This simplifies to: \[ y = 3((x - 8)^2 - 64) + 195 \]
-
Distribute the \( 3 \) and simplify: \[ y = 3(x - 8)^2 - 192 + 195 \] \[ y = 3(x - 8)^2 + 3 \]
The quadratic function in vertex form is: \[ y = 3(x - 8)^2 + 3 \]
The vertex of the parabola is at the point \( (8, 3) \).